THE APPLICATION OF RECIPROCAL TEACHING METHOD IN IMPROVING STUDENTS’ COMPREHENSION ACHIEVEMENT IN READING RECOUNT TEXT - Diny Rizki Harahap and Lidiman S.M. Sinaga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
The objective of this study is to investigate whether the application of ReciprocalTeaching Method significantly improves the students’ achievement on readingcomprehension recount text. This study was conducted by using classroom actionresearch. The subject of this research was the second grade of SMP Istiqlal Deli Tuawhich consisted of 36 students. The research was conducted in two cycles. The firstcycle consisted of three meetings and second cycle consisted of three meetings. Theinstruments for collecting the quantitative data were multiple choice and essay test forreading and the instruments for collecting the qualitative data were observation sheet,interview sheet, questionnaire sheet, and diary notes. Based on the analysis, students’achievement was improved in every test. In test I, the mean score was 67.11. In test II incycle I, the mean score was 74.67, and in the test III in cycle II, the mean score was82.78. Based on the observation sheet, interview sheet, questionnaire sheet, and diarynotes, it was found that the teaching learning process ran well. The students were moreactive and enthusiastic in working in group. It was concluded that Reciprocal TeachingMethod can improve the students’ achievement in reading recount text.